Comparative Analysis of Chloroplast Genomes of Seven Chaetoceros Species Revealed Variation Hotspots and Speciation Time - Xu, Qing; Cui, Zongmei; Chen, Nansheng (Frontiers in Microbiology, 2021)
Chaetoceros is a species-rich diatom genus with broad distribution and plays an important role in global carbon cycle and aquatic ecosystems. However, genomic information of Chaetoceros species is limited, hindering advanced researches on Chaetoceros biodiversity and their differential impact on ecology. In this study, we constructed full-length chloroplast genomes (cpDNAs) for seven Chaetoceros species, including C. costatus, C. curvisetus, C. laevisporus, C. muelleri, C. pseudo-curvisetus, C. socialis and C. tenuissimus. All of these cpDNAs displayed a typical quadripartite structure with conserved genome arrangement and specific divergence. The sizes of these cpDNAs were similar, ranging from 116,421 to 119,034 bp in size, and these cpDNAs also displayed similar GC content, ranging from 30.26 to 32.10%. Despite extensive synteny conservation, discrete regions showed high variations. Divergence time estimation revealed that the common ancestor of Chaetoceros species, which formed a monophyletic clade at approximately 58 million years ago (Mya), split from Acanthoceras zachariasii at about 70 Mya. The availability of cpDNAs of multiple Chaetoceros species provided valuable reference sequences for studying evolutionary relationship among species in the Chaetoceros species, as well as between Chaetoceros species and other diatom species.